Benthic conditions around a historic shipwreck: Vrouw Maria (1771) in the northern Baltic proper. (15th April 2015) - Ruuskanen, A.T.; Kraufvelin, P.; Alvik, R.; Díaz, E.R.; Honkonen, J.; Kanerva, J.; Karell, K.; Kekäläinen, P.; Lappalainen, J.; Mikkola, R.; Mustasaari, T.; Nappu, N.; et al.
Abstract: Since her shipwreck in 1771, the wooden vessel Vrouw Maria has been lying on the seabed at 41 m depth on the border between the Archipelago Sea and the northern Baltic proper, off the southern coast of Finland. The wreck lies in an upward position in a right angle to the dominating bottom current, which is potentially affecting seabed topography, sediment characteristics and zoobenthic communities both upstream (NE) and downstream (SW) of the wreck. This multidisciplinary study attempts to clarify abiotic and biotic patterns and processes in the vicinity of the wreck by combining field investigations with physical simulation studies in the field and in the laboratory. Multibeam echo-sounder techniques were utilised to generate a map of the wreck area and sediment grab samples were taken to characterize the sediment type and its zoobenthic community. A medium-sized field experiment generated data on the accumulation of sediment organic matter in the presence and absence of a current and/or a barrier on the seafloor and a small-scaled laboratory study was conducted to simulate scour forming processes. The results showed that a deeper basin, scour area, with the dimensions 150×300 m, was present downstream of the wreck and there was also a smaller scour area upstream of the wreck. Similar traces on the bottom were simulated in the laboratory. The organic content (recent mud) and the proportion of finer sediment were more pronounced in areas closer to both sides of the wreck. These results were in turn imitated in a field experiment, where the accumulation of organic matter in the sediment increased significantly downstream, when a current was interrupted by a barrier. Regarding zoobenthos in the wreck area, 11 taxa and a mean total abundance of 773 individuals per m 2 were registered. The dominant species were Macoma balthica and Marenzelleria sp., which together made up >80% of the total number of individuals. Multivariate data analyses showed significant differences in community structure between upstream and downstream sides of the wreck and these differences were basically expressed as more individuals upstream of the wreck of the seven most common species. Univariate data analyses also showed significantly more species and higher total abundance in the scour area upstream of the wreck compared to the downstream scour area. The weakened communities downstream of the wreck were possibly due to accumulation of organic matter and more frequent occurrence of hypoxia. The results are useful for describing bottom areas around long-term physical barriers/artificial reefs, as background measurements ahead of possibly increased archaeological diving activities, sediment excavations or measures taken to raise the wreck to the surface, as well as for any attempts to preserve the wreck in situ. Highlights: The physical presence of a wreck affected near-bottom currents and caused a scour. The scour affected surrounding sediment characteristics and infauna communities. The physical influences were simulated in the field and in the laboratory. Macrofauna communities differed between downstream and upstream sides of the wreck. The results are useful regarding fate of wrecks and impacts of artificial reefs.